TRADISI-TRADISI DALAM SHINTOO SEBAGAI PAHAM POLITHEISTIS - Oemiati, Sri (LITE, 2007)
Shintoo is a polytheistic thought with many gods and goddesses. Previously, Shintoo was an anonym collection of various nature and ancestor spirit worships that were finally be united and organized in a devotion system that is centered to the God of Ama-terasu-oo-mi-kami. In Shintoo, there are several ceremonial traditions that always be done by its followers up to now as it is believed that the tradition can bring Shintoo followers closer to their gods and goddesses.Keywords: Shintoo, norito, harai, shoogatsu, kinensai.